2005
DOI: 10.1111/j.1399-3046.2005.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post‐transplant lymphoproliferative disorder in pediatric patients: A case‐control study

Abstract: Post-transplant Lymphoproliferative Disorder (PTLD) because of the Epstein-Barr Virus (EBV) is a major concern after pediatric transplantation. The group at greatest risk is EBV-seronegative recipients who receive EBV-seropositive organs. Additional risk factors remain to be determined, including those among EBV-seropositive recipients. In this case-control study, PTLD cases were biopsy-proven over a period of 4 yr (1997-2000, inclusive). Each case was matched with 2 controls, based on the type of organ transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 25 publications
7
81
0
Order By: Relevance
“…Boyle et al reported a 43% survival among pediatric heart transplant recipients (23) and Newell et al reported 60% survival among pediatric liver transplant recipients (24), both studies published in the 1990s. Allen et al found a 2-year mortality of 36% in children with PTLD in a group of diverse organ transplants (14). More recent studies suggest improved survival after PTLD in this decade even in nonkidney organ transplants (80% in the series by Younes et al, only 18% early mortality in series of Fernandez et al; [22,25]).…”
Section: Discussionmentioning
confidence: 97%
“…Boyle et al reported a 43% survival among pediatric heart transplant recipients (23) and Newell et al reported 60% survival among pediatric liver transplant recipients (24), both studies published in the 1990s. Allen et al found a 2-year mortality of 36% in children with PTLD in a group of diverse organ transplants (14). More recent studies suggest improved survival after PTLD in this decade even in nonkidney organ transplants (80% in the series by Younes et al, only 18% early mortality in series of Fernandez et al; [22,25]).…”
Section: Discussionmentioning
confidence: 97%
“…1,5,6 Polyclonal plasma cell hyperplasia is a relatively common presentation of early PTLD, whereas frank plasmacytomas and multiple myelomas are rarely described in pediatric SOT recipients. 1 We describe a unique group of pediatric patients with EBV Ϫ plasma cell PTLDs with morphology ranging from atypical plasma cell hyperplasia to plasmacytoma-like lesions.…”
Section: Discussionmentioning
confidence: 99%
“…1 EBV seronegativity at the time of transplantation is one of the main risk factors for PTLD development, and a large number of children undergoing transplantation are EBV naive. 6 Although most PTLDs are EBV ϩ , reports of EBV Ϫ cases are increasing. 1 EBV Ϫ PTLD is more common in adults than children, tends to occur late after transplantation, and is more commonly monomorphic.…”
Section: Introductionmentioning
confidence: 99%
“…A higher mean baseline EBV load correlates with heightened risk of PTLD or recurrent PTLD (7,19). Other investigators propose combining EBV DNA measurement with a complementary test, such as EBV-specific T cell enumeration as measured by a peptide tetramer or enzyme-linked immunosorbent spot, EBV serology, reverse transcription-PCR (RT-PCR) targeting EBV transcripts, cytokine gene polymorphism, ATP release, gammopathy by serum protein electrophoresis, microarray-based expression profiles, and CD20 or CD4/CD8/NK cell counts (6,10,17,25,53,107,112,117,123,151,158,166,173,177,192,207,211,213).…”
Section: Ebv Load As a Marker Of Ptldmentioning
confidence: 99%
“…EBV is capable of driving B cell proliferation in vitro to form immortalized cell lines and also in vivo when immune surveillance is inadequate (119,179). In the setting of allogeneic transplantation when iatrogenic immunosuppression is used to prevent graft rejection, an unintended consequence is failure to suppress active EBV infection, which is accompanied by a heightened risk of developing PTLD (7,61,154,167,185,198). PTLD is a potentially life-threatening neoplasm exhibiting a spectrum of histopathologies ranging from reactive-appearing, polyclonal lymphoid infiltrates to sheets of undifferentiated cells that are morphologically indistinguishable from malignant lymphoma or plasma cell myeloma.…”
Section: Introductionmentioning
confidence: 99%